The Glp-1 Analog Liraglutide Protects Against Angiotensin II and Pressure Overload-Induced Cardiac Hypertrophy via PI3K/Akt1 and AMPKa Signaling - Li, Ran; Shan, Yingguang; Gao, Lu; Wang, Xi; Wang, Xule; Wang, Fang (Frontiers in Pharmacology, 2019)
Glp-1 analog, liraglutide (Lir), have been shown to reduce infarct size and improve cardiac function after myocardial ischaemia in rodents with or without diabetes. But the effect of Lri on angiotensin II (AngII) and pressure overload induced cardiac remodelling in non-diabetic mice and the underlying mechanism is unclear. The aim of this study is to investigate the effect of Lir on cardiac remodeling induced by AngII infusion, and explore its possible mechanism. Mice subjected to Angiotensin II as well as thoracic aorta coarctation to induce cardiac remodelling model. Mice were daily injected with either liraglutide or saline for 2 weeks. Neonatal rat cardiomyocytes and human AC cell lines were stimulated with AngII to induced cardiomyocytes remodelling model. Both in vivo and in vitro experiments indicated Lir significantly inhibited cardiac hypertrophy and improved cardiac function through directly suppressing the activation of PI3K/Akt1 and stimulating AMPKα signaling pathways. Moreover, mTOR activator (MHY1485), overexpression of constitutively active Akt, and knockdown of AMPKa2 expression all can abolish the protective effects of Lri. Moreover, the protective effects of Lri in vivo was lost in AMPKa2 knockout mice.